DISTRIBUSI DAN KEMELIMPAHAN VEGETASI LANTAI DI HUTAN PEGUNUNGAN KAMOJANG JAWA BARAT - , ULFAH SEPTIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of the research was to study distribution and abudance of floor vegetation in natural and disturbed mountain forest. The studied areas of the natural forest were Kawah Manuk (KM), Pasir Kiara (PK), and Pasir Beling (PB)